Mass Rallies: An Overview of Santri Rejection on the Five-day School Policy in Indonesia - Alnizar, Fariz (Jurnal Pendidikan Islam, 2019)
The Regulation of Ministry of Education and Culture No. 23 of 2017 concerning School Day resulted in a tremendous wave of protest. The public takes part in different sides, the pro and the contra. This research uses a hermeneutical paradigm with causal historical analysis. The results of the study show that the refusal among the pesantren community is based on a robust doctrine of the fiqh rules as a form of orthodoxy and adherence to the values taught by the pesantren. Second, the government is playing with language on its policy. In the context of full-day school regulation, the government still uses euphemism as a strategy of education political ethic. Third, Nahdlatul Ulama (NU) has a very central role in rejecting the five-day school policy.